GAMBARAN ANATOMI DAN HISTOLOGI GINJAL DAN VESIKA URINARIA PADA MUSANG LUWAK (Paradoxurus hermaphroditus) DI PULAU TIMOR - Rolens F. M. Bani; Filphin A. Amalo; Yulfia N Selan (Jurnal Veteriner Nusantara, 2020)
Asian palm civet (Paradoxurus hermaphroditus) also known as toddy cat or Asian palm civet. Urinary system is a system that plays an important role in cleaning products that are not useful in the body, the cleaning process includes all products that dissolve in the blood, transporting all the material out of the body and also eliminate excess water in the body. The purpose of this research was to observe the structure of the anatomy and histology of kidney and urinary bladder the asian palm civet. Three Asian palm civets were used in this study. Asian palm civets were anaesthetized and perfused then opened the abdomen to observe the anatomy of kidneys and urinary bladder. The anatomy of kidney and urinary bladder representation showed that the asian palm civet had 3 parts: the renal cortex, renal medulla and renal pelvis. The mean length, width and weight of toddy cat kidney was 1.80 ± 0.1 cm, 1.16 ± 0.15 cm and 1.43 ± 0.15 g respectively. Meanwhile, renal histology with Hematoxiline Eosin staining (HE) showed the glomerulus, Bowman's capsule, urinary space, proximal convoluted tubule, distal convoluted tubule, and macula densa. Overview anatomy bladder Asian palm civets (Paradoxurus hermaphroditus) had conical with a strong and flexible muscles when pulled. The mean length, width and weight of the bladder for urine unallocated was 2.43 ± 0.15 cm, 1.7 ± 0.1 cm, and 1.13 ± 0.2 g respectively. Meanwhile, the bladder looks epithelial histology transisional, longitudional and circular muscle smooth and connective tissue.